25 years (1981–2005) of equilibrium-line altitude and mass-balance reconstruction on Glacier Blanc, French Alps, using remote-sensing methods and meteorological data - Rabatel, Antoine; Dedieu, Jean Pierre; Thibert, Emmanuel; Letréguilly, Anne; Vincent, C. (Journal of Glaciology, 2008)
[Departement_IRSTEA]RE [TR1_IRSTEA]RIE / ALPRISK International audience Annual equilibrium-line altitude (ELA) and surface mass balance of Glacier Blanc, Ecrins region, French Alps, were reconstructed from a 25 year time series of satellite images (1981–2005). The remote-sensing method used was based on identification of the snowline, which is easy to discern on optical satellite images taken at the end of the ablation season. In addition, surface mass balances at the ELA were reconstructed for the same period using meteorological data from three nearby weather stations. A comparison of the two types of series reveals a correlation of r > 0.67 at the 0.01 level of significance. Furthermore, the surface mass balances obtained from remote-sensing data are consistent with those obtained from field measurements on five other French glaciers (r ¼ ¼ 0.76, p < 0.01). Also consistent for Glacier Blanc is the total mass loss (10.8mw.e.) over the studied period. However, the surface mass balances obtained with the remote-sensing method show lower interannual variability. Given that the remote-sensing method is based on changes in the ELA, this difference probably results from the lower sensitivity of the surface mass balance to climate parameters at the ELA.